The Effect of Hand Massage on Reducing the Anxiety Level of Pre-Surgery Clients in Tangerang City Regional Public Hospital - Nasihin Nasihin (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Surgical procedures are important events in human life which complex and stressful. When hearing the word surgery, patients face situations that can cause fear, worry, helplessness, and anxiety. Surgical procedures may cause psychological and physical problems in patients undergoing surgery. Waiting in the preparation room is the most worrying moment for a patient undergoing a surgical procedure. The patient is faced with a situation where the patient is under a high level of anxiety. This study aimed to determine the effect of hand massage on reducing anxiety levels in pre-surgery clients at Tangerang City Regional Public Hospital. This study used a quantitative design with a quasi-experimental approach; a study provides treatment (intervention) and measures the effects of treatment. The approach technique was a one-group pre-test and post-test. The total number of study participants was 18 people. The study utilized a simple random sampling. The results showed that giving hand massage interventions could reduce anxiety levels by 8.2, from 58.3 to 50.1 after a hand massage. The results of the T-test obtained a p-value of 0.001. It was concluded that there was a significant difference between the level of anxiety before and after giving the hand massage intervention. It is recommended to conduct further research with a different approach.